2016
DOI: 10.3389/fpls.2016.01595
|View full text |Cite
|
Sign up to set email alerts
|

Search for Nodulation and Nodule Development-Related Cystatin Genes in the Genome of Soybean (Glycine max)

Abstract: Nodulation, nodule development and senescence directly affects nitrogen fixation efficiency, and previous studies have shown that inhibition of some cysteine proteases delay nodule senescence, so their nature inhibitors, cystatin genes, are very important in nodulation, nodule development, and senescence. Although several cystatins are actively transcribed in soybean nodules, their exact roles and functional diversities in legume have not been well explored in genome-wide survey studies. In this report, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In this report, 6 cystatins were identified from our RNA-Seq ( Table S5 ), among them, two cystatins (Glyma18g12240 and Glyma18g00690) were not in the seven cystatins 11 . Glyma18g12240 was significantly increased in roots at 0.5 h of post inoculation and during nodule developments 58 and different expressed in 6 Groups ( Table S5 ), indicating that Glyma18g12240 play roles in nodulation and nodule development. The symbiotic function of Glyma18g12240 was studied and the results showed that it really promotes nodulation in L. japonicus and performs an essential role in delaying nodule senescence ( Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this report, 6 cystatins were identified from our RNA-Seq ( Table S5 ), among them, two cystatins (Glyma18g12240 and Glyma18g00690) were not in the seven cystatins 11 . Glyma18g12240 was significantly increased in roots at 0.5 h of post inoculation and during nodule developments 58 and different expressed in 6 Groups ( Table S5 ), indicating that Glyma18g12240 play roles in nodulation and nodule development. The symbiotic function of Glyma18g12240 was studied and the results showed that it really promotes nodulation in L. japonicus and performs an essential role in delaying nodule senescence ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that cysteine proteases and cystatins are actively transcribed during nodule development and senescence 11 , and inhibition of some cysteine proteases delay nodule senescence 56 57 . Cystatin genes, nature inhibitors of cysteine proteases, are very important in nodule symbiosis and 7 soybean cystatins play different roles in nodulation, nodule development and senescence 58 . In this report, 6 cystatins were identified from our RNA-Seq ( Table S5 ), among them, two cystatins (Glyma18g12240 and Glyma18g00690) were not in the seven cystatins 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The symbiosis-related soybean C2H2s selected from our previous RNA-seq data (Yuan et al, 2016a , 2017 ) were further evaluated using qPCR, and the methods refer to our previous studies (Yuan et al, 2016b ). Briefly, purified RNA samples were treated with DNase I (Takara) and reversely transcribed into cDNA using a Prime Script RT reagent Kit (Perfect Real Time) with gDNA Eraser (Takara Bio, Inc) and oligo (dT) as the primer.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the molecular mass (11.4 kDa) and other molecular characteristics of BnCPI (described above), we concluded that it should be clustered into group I. Subgroups (Group I, Group II and Group III) of the phytocystatin family were generated on the basis of phylogenetic analysis [ 31 ]. Introns are common in the coding regions of cystatins from plants and animals, and some phytocystatins contain more than one intron [ 32 , 33 , 34 , 35 ]. Intron–exon structure is also often used to characterize cystatin genes; those lacking introns in their ORF are categorized as MCOG C, whereas those containing three introns are classed into subgroup B1, and those with only one intron in the DNA sequence—located between the coding sequences for the conserved motifs LARFAV and QxVxG—are placed in either MCOG A or subgroup B2 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%